Sjögren-Larsson syndrome. Pathogenic variant analysis of ALDH3A2 gene in six Iranian families. - Ahmadi, S.; Davoudi-Dehaghani, E.; Bagherian, H.; Jamali, P.; Shirzad, T.; Ramezan, F.; Jamali, M.; Vahidnezhad, H.; Zeinali, S. (European Journal of Pediatric Dermatology, 2019)
Sjögren-Larsson syndrome (SLS) is a rare autosomal recessive disorder. The actual study is aimed at performing pathogenic variant analysis of ALDH3A2 gene in Iranian patients with SLS. The study was performed on six SLS families in Iran. All the patients had consanguineous parents. A medical history was obtained from the families and clinical examination was carried out on the patients. Sanger sequencing was used to analyse all exons of ALDH3A2 gene and their boundary regions. Co-segregation analysis of the identified variants with the disease was performed in each family. A novel variant c.1253delC and three reported pathogenic variants c.798+5G>A, c.943C>T and c.683G>A were found in these families. A pathogenic variant was detected in half of the families. The identification of common pathogenic variants in the ALDH3A2 gene in Iran can be helpful to design a proper diagnostic test for SLS in this country. More studies are needed to characterize variants responsible for this disease in Iran.